Hemostasis in neonatal ECMO - Cortesi, Valeria; Raffaeli, Genny; Amelio, Giacomo S.; Amodeo, Ilaria; Gulden, Silvia; Manzoni, Francesca; Cervellini, Gaia; Tomaselli, Andrea; Colombo, Marta; Araimo, Gabriella; Artoni, Andrea; Ghirardello, Stefano; et al. (Frontiers in Pediatrics, 2022)
Extracorporeal membrane oxygenation (ECMO) is a life-saving support for cardio-respiratory function. Over the last 50 years, the extracorporeal field has faced huge technological progress. However, despite the improvements in technique and materials, coagulation problems are still the main contributor to morbidity and mortality of ECMO patients. Indeed, the incidence and survival rates of the main hemorrhagic and thrombotic complications in neonatal respiratory ECMO are relevant. The main culprit is related to the intrinsic nature of ECMO: the contact phase activation. The exposure of the human blood to the non-endothelial surface triggers a systemic inflammatory response syndrome, which chronically activates the thrombin generation and ultimately leads to coagulative derangements. Pre-existing illness-related hemostatic dysfunction and the peculiarity of the neonatal clotting balance further complicate the picture. Systemic anticoagulation is the management’s mainstay, aiming to prevent thrombosis within the circuit and bleeding complications in the patient. Although other agents (i.e., direct thrombin inhibitors) have been recently introduced, unfractionated heparin (UFH) is the standard of care worldwide. Currently, there are multiple tests exploring ECMO-induced coagulopathy. A combination of the parameters mentioned above and the evaluation of the patient’s underlying clinical context should be used to provide a goal-directed antithrombotic strategy. However, the ideal algorithm for monitoring anticoagulation is currently unknown, resulting in a large inter-institutional diagnostic variability. In this review, we face the features of the available monitoring tests and approaches, mainly focusing on the role of point-of-care viscoelastic assays in neonatal ECMO. Current gaps in knowledge and areas that warrant further study will also be addressed.